2015
DOI: 10.1371/journal.pone.0125617
|View full text |Cite
|
Sign up to set email alerts
|

OXPHOS-Mediated Induction of NAD+ Promotes Complete Oxidation of Fatty Acids and Interdicts Non-Alcoholic Fatty Liver Disease

Abstract: OXPHOS is believed to play an important role in non-alcoholic fatty liver disease (NAFLD), however, precise mechanisms whereby OXPHOS influences lipid homeostasis are incompletely understood. We previously reported that ectopic expression of LRPPRC, a protein that increases cristae density and OXPHOS, promoted fatty acid oxidation in cultured primary hepatocytes. To determine the biological significance of that observation and define underlying mechanisms, we have ectopically expressed LRPPRC in mouse liver in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…This suggests lower NAD + bioavailability, which would be unfavorable for the 3-hydroxyacyl-CoA-dehydrogenase activity. The importance of the liver in eliciting the observed plasma metabolite changes, including hydroxylated ACs, is supported by our findings in H-Lrpprc -/mice, and previous studies documenting impaired LCFA oxidation in liver mitochondria (14)(15)(16). Conversely, overexpression of Lrpprc in mouse liver improved LCFA oxidation and was accompanied by increased hepatic OXPHOS and tissue NAD + levels (16).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This suggests lower NAD + bioavailability, which would be unfavorable for the 3-hydroxyacyl-CoA-dehydrogenase activity. The importance of the liver in eliciting the observed plasma metabolite changes, including hydroxylated ACs, is supported by our findings in H-Lrpprc -/mice, and previous studies documenting impaired LCFA oxidation in liver mitochondria (14)(15)(16). Conversely, overexpression of Lrpprc in mouse liver improved LCFA oxidation and was accompanied by increased hepatic OXPHOS and tissue NAD + levels (16).…”
Section: Discussionsupporting
confidence: 87%
“…Lipidomics and molecular analyses in the H-Lrpprc -/mouse corroborate the plasma lipid dyshomeostasis of LSFC patients, including lower plasmalogens, and unveil a role of the liver. The H-Lrpprc -/mouse model, which harbors a liver-specific loss of function of Lrpprc, was previously investigated and shown to display at 5 weeks major mitochondrial bioenergetic defects in the liver, which are characteristic of LSFC patients (>90% and 80% lower protein levels for LRPPRC and COX subunit COX1, respectively), and to recapitulate histopathological changes characteristic of microvesicular steatohepatitis (15,16). In the present study, we used H-Lrpprc -/mice that had reached 14 weeks of age, and confirmed lower protein levels in liver for LRPPRC and COX subunit MTCO1 (60% and 30%, respectively; Supplemental Figure 3), although the observed changes were less pronounced than at 5 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b and Supplementary Table S3). Fatty acid oxidation requires NAD + , which induces fatty acid oxidation to generate ATP40. Moreover, NAD + can activate the upstream signaling pathway of fatty acid oxidation by activation of SIRT1, a NAD + -dependent protein deacetylase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the studies of Tran et al did not examine whether restoration of cellular NAD ultimately preserved mitochondrial NAD concentrations, mitochondrial oxidative phosphorylation, or ATP production. Further, it is also possible that other beneficial effects of PGC1/ such as mitochondrial biogenesis can act in other contexts to preserve mitochondrial oxidative phosphorylation leading to restoration of NAD concentrations [5].…”
mentioning
confidence: 99%